Derechos de los adolescentes comprendidos entre quince y dieciocho años que ejercen el trabajo por cuenta propia. - Arboleda Toabanda, Evelyn Lizbeth (2024)
In the context of the rights of adolescents aged 15 to 18 who engage in self-employment, it is crucial to consider national and international legislation, as well as agreements protecting minors in the labor sector, it sets the focus of the present research, emphasizing that child labor is prohibited due to the risks it poses to the physical, mental well-being, and overall development of minors, including their education. Therefore, it is essential to analyze this practice in the context of adolescent rights, ensuring the respect of their fundamental rights. The work of adolescents is increasing daily in societies, and the Ecuadorian state is no exception. While it is true that the highest norm of the state, which is the Constitution of the Republic, designates adolescents as part of the population group that must be comprehensively cared for and protected due to their significance for the state's development. The severe social conditions we currently face have left adolescents in our society with no way out. To contribute to their families and secure individual sustenance, they engage in various tasks, one of which is self-employment. Unfortunately, in many cases, this form of work is not respected by state entities or by those who exploit this labor force to obtain the lowest cost, violating the human and labor rights of adolescents involved in self-employment. Adolescents engaged in self-employment must have their fundamental rights guaranteed, including the right to education, a safe and healthy working environment, and protection against exploitation. It is essential for laws and international agreements to be rigorously enforced to prevent the labor exploitation of these adolescents. Furthermore, mechanisms should be established to ensure that their voices are heard and considered in 6 all decisions affecting them. The rights-based approach and participation of adolescents can provide guidance to ensure the effective development of their rights and address accountability needs regarding engagement in self-employment during this stage of life. To conduct this investigative analysis, it is necessary to start from doctrinal conceptualizations of the proposed topic, referring to literature, infographics, and the use of various tools that allow for contrasting criteria and supporting the current project. Ultimately, this process aims to draw conclusions and provide recommendations within a legal context. The research methodology is qualitative, employing the dogmatic and interpretative approach to constitutional and legal norms. Through these methods, a response to the addressed problem is derived from the best possible reconstruction allowed by the legal material available. Additionally, since the social phenomena studied in this work are measurable and quantifiable, I will measure and establish causal relationships between variables to explain the study's problem and the current social reality. Keywords: Adolescent Rights, Comprehensive Protection, Adolescents, Self-Employment, Participation.